A comparison of the behaviour and survival of angling vs. trap‐sampled Salmo salar smolts. Issue 3 (5th July 2022) - Kennedy, Richard; Rosell, Robert; Campbell, Warren; Allen, Michelle; Del Villar‐Guerra, Diego
Abstract: An experiment was undertaken, using acoustic telemetry, to compare the survival and migratory timing of Salmo salar L. smolts sampled, under optimal conditions, in a traditional fixed Wolf trap against a sample of rod‐caught fish captured using a sensitive angling technique. No significant difference was evident in survival with 83% of both samples detected in the river outflow, 67% of the trap and 76% of the rod samples were detected in coastal waters and finally 43% of the trap and 35% of the rod samples were detected on an offshore array c. 50 km from the river outlet. No significant difference was evident in the time taken for trap‐ and rod‐sampled fish to reach either the river outflow, coastal or offshore waters. Angling, if undertaken sensitively, can provide an effective, resource‐efficient and ethically justifiable sampling tool for juvenile salmonid age classes.